Evaluasi Distributed Control System pada PLTU dengan Failure Mode, Effect and Criticaly Analysis (FMECA) - Saputra Dwi Nugroho (Sekolah Tinggi Teknik - PLN, 2022)
Steam power plants (PLTU) are power plants that have the largest percentage of power plants owned by PLN. The main controller in a PLTU usually uses a Distributed Control System (DCS). The reliability of DCS in a PLTU must be maintained properly so that the power plant does not experience a control failure that causes the PLTU to stop suddenly. DCS PLTU Sebalang Unit 1 has used the FMEA method to determine its maintenance strategy, but the FMEA has not defined the function of the equipment, functional failure, the effect of failure, and criticality analysis (CA) of the equipment. failure mode prioritization has not been carried out. With the FMECA conducted in this study, the priority of the failure mode can be carried out effectively so that the priority determination of DCS maintenance can be carried out. Results of the FMECA that have been carried out, it is known that the failure that occurs in the DCS CPU has the highest RPN value (140). The maintenance strategy obtained from the FMECA results is preventive maintenance (PM), namely: 1) checking the power supply voltage, 2) checking the communication status, idle time status, load and CPU status, and maintenance run to failure (RTF) CPU replacement if there is damage to the CPU. FCS CPUs.